Gill parasites of Cephalopholis argus (Teleostei: Serranidae) from Moorea (French Polynesia): site selection and coexistence - Lo, C M; Morand, S (Folia parasitologica, 2001)
The distribution and coexistence of gill ectoparasites of 121 specimens of Cephalopholis argus Bloch et Schneider, caught between October 1994 and October 1995, were investigated. Adults of the monogenean Benedenia sp. and copepod Hatschekia sp., the larval caligid copepod Caligus sp. (copepodite and chalimus stages), and praniza larvae of the isopod Gnathia sp. were found. All species were aggregated within the host population. Infracommunities were poor, with only 40.5% of fish infected by two parasite species. Only two individual fish harboured all the parasite species observed at the component community level. Prevalences were less than 50% and mean intensities were low (less than 6 parasites/host). No dominant parasite species were observed in the host population. The spatial distribution of each parasite species was studied on different partitions of the gill arches. Adult parasite stages that are mobile showed much overlap in their distribution, whereas temporarily attached larvae of Caligidae were more site specific. Copepodite and chalimus larvae showed niche restriction that is probably due to gregarious behaviour. Positive associations between caligid larvae reflected intraspecific interaction for site and/or resources. Each of the Caligus sp. larval stages prefers specific sites, as do the adults, which occur exclusively in the buccal cavity of the host. Infracommunities were too poor and too few to induce processes of interspecific competition.
Keywords: druhová specificita; Animals; Trematoda; Polynesia; Gills; infestace ektoparazity; zvířata; Ectoparasitic Infestations; Host-Parasite Interactions; Species Specificity; interakce hostitele a parazita; korýši; žábry; Crustacea; Statistical Distributions; Polynésie; statistická rozdělení